The relationship between intellectual capital information and firms’ market value: a study from an emerging economy - Ousama, Abdulrahman Anam; Al-Mutair, Mashael Thaar; Fatima, Abdul Hamid (Emerald Group Publishing Ltd., 2019)
Purpose: The purpose of this paper is to investigate the relationship between the intellectual capital (IC) information reported in the annual reports and market value of the companies listed on the Qatar Stock Exchange. Design/methodology/approach: The study is based on a panel data collected from the annual reports and Bloomberg database for six years, specifically the periods 2010-2012 and 2016-2018. The total sample consists of 252 observations. The theoretical framework was developed in reference to the resource-based theory. The regression model is based on Ohlson’s model, which has been modified by including IC information. Findings: The study found that there is a significant relationship between IC information and firm market value. This finding indicates that companies report their IC to help the stakeholders (e.g. shareholders, investors) to understand the real value of the company (which includes IC values). Practical implications: The shift to a knowledge-based economy (KBE) has made knowledge a driver for economic growth, and it has become more important than capital, land and labour. This shift makes IC and resources vital for companies to create wealth, value and gain competitive advantage. The State of Qatar plans to transform its economy to a KBE in its “Qatar Vision 2030”. The findings of the study show that the companies have started to depend more on IC to contribute to transforming Qatar’s economy to a KBE. Originality/value: This study could be considered a pioneer study to examine the association of IC disclosure and firm value in Qatar. Furthermore, prior literature has mixed findings, which justifies further investigation of IC’s effect on market value, particularly in the emerging economy of Qatar. © 2019, A.A. Ousama, Mashael Thaar Al-Mutairi and A.H. Fatima.